Effect of activated charcoal in reducing paracetamol absorption at a supra-therapeutic dose - Winai Wananukul (2018)
Background: Activated charcoal (AC) is recommended for treatment of acute poisoning, thereby decreasing gastrointestinal tract absorption. AC from different sources may have different adsorptive capacity. The AC that is available in Thailand has not been proven yet for its efficacy. The authors simulated paracetamol overdose model for the present study. Objective: To assess the efficacy of AC that is available in Thailand in decreasing absorption of paracetamol at supratherapeutic dose. Material and Method: This was a two-arm, prospective, crossover study. Washout period was 1 week. Twelve healthy male volunteers participated. All volunteers were randomly assigned to either sequence of control-experiment (CE) or EC. The participants ingested 60 mg/Kg of paracetamol at Time = 0. At Time = 0.25 hour, they ingested 50 g of AC as slurry with 250 ml of water when they were assigned as E, but drank 250 mL of water when were assigned as C. Blood samples were serially collected for determination of paracetamol concentration and calculating pharmacokinetic parameters, area under the timeconcentration curve (AUC (0,∞)). Results: Means of the AUC (0,∞) were 313.7 ± 29.8 and 184.8 ± 91.6 mg-h/L in the control and experimental arm, respectively. It was statistically different (p = 0.01). Conclusion: The tested AC was found to be able to reduce the absorption of the supratherapeutic dose of paracetamol.